Killing Patton [large type] : the strange death of World War II's most audacious general - O'Reilly, Bill; Dugard, Martin (Wheeler Publishing, a part of Gale, Cengage Learning, 2014)
General George S. Patton, Jr. died under mysterious circumstances in the months following the end of World War II. For almost seventy years, there has been suspicion that his death was not an accident--and may very well have been an act of assassination. "Killing Patton" takes readers inside the final year of the war and recounts the events surrounding Patton's tragic demise, naming names of the many powerful individuals who wanted him silenced.